USE OF NUMBERED HEADS TOGETHER TECHNIQUE TO IMPROVE READING COMPREHENSION OF JUNIOR HIGH SCHOOL STUDENTS - Herawati, Titin (Borneo Journal of English Language Education, 2019)
The purpose of this research was to find out whether Numbered Heads Together technique can improve students’ reading comprehension at seventh grade students’ of SMPN 7 Tarakan. This research was in the form of Pre-experiment. The researcher tried to find out the differences before and after teaching by numbered heads together technique. The subject of this study was students in grade 7-2 which consisted of 29 students at SMPN 7 Tarakan in academic year 2018/2019. The instruments were reading tests that included pre-test and post test. To analyze, the researcher used descriptive analysis and SPSS 22.0 for statistical analysis. The result of this study indicated that there were differences between pre-test and post test. It was proven by the results of the students mean score. The students’ mean score in pre-test were 45,51 and 54,13 at the post test. It means the improvement of the students’ mean score was 8,62. The score in post test was higher than the pre-test scores. It showed that there was a significant difference from students’ reading score on pre-test and post test. The results of the paired sample test indicate that the t-test (2.819) was higher that the t-table (2.048). In this research, the researcher found there was significant differences from the use of NHT technique in learning. This technique was able to improve students’ enthusiasm, helped students understand the text easily, and builded students critical thinking. Then it can be concluded that the NHT technique has proven to be an effective technique for increasing reading comprehension in seventh grade students’ of SMPN 7 Tarakan.